2021
DOI: 10.1002/ar.24732
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic signaling in prefrontal cortex contributes to the antidepressant effect of electroacupuncture: An iTRAQ‐based proteomics analysis in a rat model of CUMS

Abstract: Electroacupuncture (EA) is used as an adjunctive treatment for depression.This study was conducted to evaluate the efficacy and mechanisms of EA in the depressive rat model induced by chronic unpredictable mild stress (CUMS) in male adult Wistar rats. The underlying mechanisms were explored by using isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomic analysis of the proteins in the prefrontal cortex (PFC), and observing the number of the PFC neurons stained with hematoxylin and eosin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Based on our former research, 19 we further explored the vmPFC in CUMS rats in this study, now that the PFC is noteworthy for the realization of mood, learning, memory, execution, information integration, and other functions. The vmPFC in PFC integrates information from other brain regions such as the amygdala, striatum, ventral tegmental area (VTA), and temporal lobe, leading to the generation of negative emotions, self‐awareness, and self‐reflection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our former research, 19 we further explored the vmPFC in CUMS rats in this study, now that the PFC is noteworthy for the realization of mood, learning, memory, execution, information integration, and other functions. The vmPFC in PFC integrates information from other brain regions such as the amygdala, striatum, ventral tegmental area (VTA), and temporal lobe, leading to the generation of negative emotions, self‐awareness, and self‐reflection.…”
Section: Discussionmentioning
confidence: 99%
“…The vmPFC receives neural projection from many other regions and is involved in one of the four dopaminergic pathways (the mesocortical pathway, connecting the ventral tegmentum to the PFC). Given our previous isobaric tags for relative and absolute quantitation (iTRAQ) finding of dopaminergic changes in the PFC, 19 the dopamine‐related mechanism in the vmPFC may be contributing to the alleviation of depressive symptoms.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, these two acupoints are frequently used in combination for the treatment of depression [ 74 , 75 ]. Studies using samples from the prefrontal cortex have found that EA can alleviate symptoms of pleasure deficit, increase the number of PFC neurons and modulate dopaminergic signaling pathways to treat depression [ 76 ]. Analysis of the KEGG pathway revealed seven significantly enriched pathways in which the dopaminergic synapse, cocaine addiction, amphetamine addiction, and alcoholism pathways share the same four upregulated proteins.…”
Section: Application Of Proteomics In Acupuncture Researchmentioning
confidence: 99%
“…KEGG pathway enrichment analysis suggested that oxidative phosphorylation was a major factor involved in the effects of EA therapy on DPN. [ 76 ] BCP EA ST36 BL60 30 min, 7/week, 1 weeks SD rats; the L4–L6 DRGs PEX100 protein microarray (antibody array); WB validation 176 DEPs 1. EA alleviated mechanical pain behavior and to some extent bone destruction in BCP rats.…”
Section: Application Of Proteomics In Acupuncture Researchmentioning
confidence: 99%